2021
DOI: 10.1093/gigascience/giaa148
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-level reference genome of the European wasp spiderArgiope bruennichi: a resource for studies on range expansion and evolutionary adaptation

Abstract: Background Argiope bruennichi, the European wasp spider, has been investigated intensively as a focal species for studies on sexual selection, chemical communication, and the dynamics of rapid range expansion at a behavioral and genetic level. However, the lack of a reference genome has limited insights into the genetic basis for these phenomena. Therefore, we assembled a high-quality chromosome-level reference genome of the European wasp spider as a tool for more in-depth future studies. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 88 publications
2
24
0
2
Order By: Relevance
“…From the available genomes, we selected those with a contig-N50 above 8,000 bp in order to avoid genomes that were highly fragmented. This included the genomes of S. mimosarum ( Sanggaard et al 2014 ), L. hesperus (BCM-HGSC website), P. tepidariorum ( Gendreau et al 2017 ), T. clavipes ( Babb et al 2017 ), D. silvatica ( Sánchez-Herrero et al 2019 ), A. ventricosus ( Kono et al 2019 ) and A. bruennichi ( Sheffer et al 2021 ). Additionally, we downloaded the genome of the bark scorpion C. sculpturatus ( Schwager et al 2017 ) as an outgroup.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the available genomes, we selected those with a contig-N50 above 8,000 bp in order to avoid genomes that were highly fragmented. This included the genomes of S. mimosarum ( Sanggaard et al 2014 ), L. hesperus (BCM-HGSC website), P. tepidariorum ( Gendreau et al 2017 ), T. clavipes ( Babb et al 2017 ), D. silvatica ( Sánchez-Herrero et al 2019 ), A. ventricosus ( Kono et al 2019 ) and A. bruennichi ( Sheffer et al 2021 ). Additionally, we downloaded the genome of the bark scorpion C. sculpturatus ( Schwager et al 2017 ) as an outgroup.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the advances in spider ecology, evolution, and systematics, knowledge of spider genomes still lags relative to other taxa. Most of the available spider genomes are of poor quality, being highly fragmented ( Garb et al 2018 ) and lack a substantial part of the genome, with only three recent exceptions involving chromosome-resolved genomes ( Escuer et al 2021 ; Fan et al 2021 ; Sheffer et al 2021 ). Several factors contribute to the sparse availability of high-quality spider genome assemblies, including the lack of a model organism among spiders (sensu Drosophila melanogaster in flies and Tribolium castaneum in beetles) ( Brewer et al 2014 ), and the challenges associated with sequencing spider genomes, which are characterized by high AT-content, repeats, heterozygosity, and often large genome sizes ( Garb et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second phylogenetic analysis only a subset of closely related Pax subfamilies was used (Pax2/5/8, Pax6, and poxn). Using the candidates for the respective groups recovered from P. tepidariorum, D. rerio Pax2/5/8 as well as D. melanogaster Pax2, poxn, and Pax6 orthologs were used to search for similar sequences in more chelicerate genomes including the xiphosuran Limulus polyphemus, and the spiders Argiope bruennichi (Sheffer et al, 2021), Stegodyphus dumicola (Liu et al, 2019) and Araneus ventricosus (Kono et al, 2019). Again, only unique hits with an e-value threshold lower than e-50 were kept (except for the xiphosuran L. polyphemus, for which only hits lower than e-100 were kept because of the large number of candidate hits).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Several recombinant studies have demonstrated that functional silk fibers, albeit with diminished mechanical properties, can be produced from the transgenic expression of constructs containing only the terminal and limited repetitive sequence from a single spidroin (Adrianos et al, 2013;Brooks et al, 2008;Heidebrecht et al, 2015;Saric et al, 2021;Xia et al, 2010;You et al, 2018). Second, recent advances in genomic technologies have made possible the discovery of complete silk gene sequences, which were previously inaccessible (Babb et al, 2017;Kono et al, 2019;Sheffer et al, 2021;Stellwagen and Burns, 2021;Stellwagen and Renberg, 2019;Zhou et al, 2021). Genomic comparisons coupled with our biomechanical tests will allow us to understand S1 and S2.…”
Section: Conditional Performance Of Structural Materialsmentioning
confidence: 99%